Hubungan Kejadian Hipertensi dengan Fungsi Kognitif Lansia: Relationship between Hypertension and Cognitive Function in the Elderly - Hilda Iryana Atika Khan; Suwanti (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Ngudi Waluyo, 2023)
High blood pressure as a chronic disease called the silent killer. It is as one of the etiology of decreased cognitive function, it worsens condition of cognitive function. Knowing the correlation the hypertension incidence with cognitive function among elder people in Branjang West Ungaran District. Descriptive correlatif used cross sectional approach. The population were 60 elderly with hypertension. Method of sampling used total sample with a 60 elderly. The instrument was secondary data and the MMSE. Bivariate analysis used Rank-Spearman. This study state most of elderly who experienced hypertension at stage 1 were 34 respondents (56.7%). There were 26 respondents (43.3%) with definite cognitive impairment, 21 respondents (35.0%) with probable cognitive impairment, and 13 respondents (21.7%) with normal cognitive function. There was a significant correlation between the incidence of hypertension and cognitive function in the elderly in Branjang village West Ungaran District with p-value = 0.002 (<0.05), r = -0.399, which means that with a strong enough correlation in the category. The elderly need to pay attention to their blood pressure so that their hypertension is controlled by adjusting their lifestyle and attending the elderly health unit so that cognitive function decline does not occur. ABSTRAK Hipertensi dikenal sebagai penyakit yang membunuh secara diam-diam. Hipertensi adalah salah satu penyebab gangguan kognitif dan memperburuk kondisinya. Menganalisa korelasi antara kejadian hipertensi dan fungsi kognitif lansia di Branjang,Ungaran Barat. Deskriptif korelasi dengan cross sectional approach. Populasi yaitu lansia penderita hipertensi sebanyak 60. Sampel diambil dengan total sampel sebanyak 60 lansia. Instrumen dengan data sekunder dan tool MMSE. Analisa bivariat menggunakan Rank-Spearman. Sebagian besar lansia mengalami hipertensi stadium 1 sejumlah 34 lansia (56,7%)yang mengalami hipertensi paling banyak pada stadium 1 sebanyak 34 responden (56,7%). Definite gangguan kognitif sejumlah 26 lansia (43,3%), probable sejumlah 21 responden (35 %), dan kategori normal sejumlah 13 lansia (21,7%). Ada korelasi signifikan antara kejadian hipertensi dan fungsi kognitif lansia dengan p-value = 0,002 (<0,05), r = -0,399 yang artinya terdapat hubungan yang signifikan antara kejadian hipertensi dengan fungsi kognitif pada lansia, dengan kekuatan korelasi dalam kategori cukup kuat. Lansia perlu memperhatikan hipertensinya supaya terkontrol melalui mengatur life style, mengikuti posyandu lansia sehingga tidak terjadi penurunan fungsi kognitif